The Manasseh Hill Country Survey Volume 7 : The South-Eastern Samaria Shoulder, from Wadi Rashash to Wadi 'Aujah - Bar, Shay, (Culture and History of the Ancient Near East ;, 2022)
The book presents the results of a complete detailed survey of the eastern region of Samaria, mainly the South-Eastern Samaria Shoulder, from Wadi Rashash to Wadi 'Aujah within the territory of Israel/Palestine. This project, in progress since 1978, and covering 2500 sq. km, is a thorough, metre-by-metre mapping of the archaeological-historical area between the River Jordan and the Sharon Plain, and between Nahal 'Iron and the north-eastern point of the Dead Sea. This territory is one of the most important in the country from the Biblical and archaeological view; and the survey is a valuable tool for scholars of the Bible, Archaeology, Near Eastern history, tourism, and other aspects of the Holy Land.